2020
DOI: 10.1111/all.14491
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor‐α signaling increases allergen‐induced IL‐33 release and airway inflammation

Abstract: Background: Group 2 innate lymphoid cells (ILC2) are stimulated by IL-33 to increase IL-5 and IL-13 production and airway inflammation. While sex hormones regulate airway inflammation, it remained unclear whether estrogen signaling through estrogen receptor-α (ER-α, Esr1) or ER-β (Esr2) increased ILC2-mediated airway inflammation. We hypothesize that estrogen signaling increases allergen-induced IL-33 release, ILC2 cytokine production, and airway inflammation. Methods: Female Esr1-/-, Esr2-/-, wild-type (WT), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 61 publications
(201 reference statements)
0
31
0
2
Order By: Relevance
“…5 ). This contrasted with the observation that ILC2 numbers and function were up-regulated in mice constitutively lacking ERα [ 50 , 51 ]. This was however explained by the elevated seric testosterone levels produced by the ovaries in ERα −/- female [ 51 ].…”
Section: Biological Impact Of Sex-hormone Signaling On Ilcsmentioning
confidence: 65%
See 3 more Smart Citations
“…5 ). This contrasted with the observation that ILC2 numbers and function were up-regulated in mice constitutively lacking ERα [ 50 , 51 ]. This was however explained by the elevated seric testosterone levels produced by the ovaries in ERα −/- female [ 51 ].…”
Section: Biological Impact Of Sex-hormone Signaling On Ilcsmentioning
confidence: 65%
“…This phenotype was associated with a reduction of lung inflammation upon allergen challenge, and a reduction of cytokine production by ILC2 in male mice, indicating that androgens may not only affect ILC2 development and maintenance in tissues, but also their function [ 54 , 82 ]. It has been suggested that IL-33 expression could be differentially regulated between female and male mice, with estrogens-dependent upregulation in female [ 50 , 54 ]. However, the sex bias in lung ILC2 numbers and phenotypic changes are not affected by IL-33 deficiency [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with wild-type Esr1-/- mice, those stimulated by Alternaria extract (Alt Ext) exhibited fewer IL-33eGFP+ epithelial cells, reduced IL-33 release, reduced secretion of IL-5 and IL-13 and fewer bronchoalveolar lavage (BAL) eosinophils. It has been suggested that ER-α (Esr1) signaling increases the release of IL-33 and ILC2-mediated airway inflammation ( 55 ).…”
Section: Initiation Of the Ilc2 Response During Allergic Reactionsmentioning
confidence: 99%